Intrinsic IL-2 production by effector CD8 T cells affects IL-2 signaling and promotes fate decisions, stemness, and protection - Kahan, Shannon M; Bakshi, Rakesh K; Ingram, Jennifer T; Hendrickson, R Curtis; Lefkowitz, Elliot J; Crossman, David K; Harrington, Laurie E; Weaver, Casey T; Zajac, Allan J (Science immunology, 2022)
Here, we show that the capacity to manufacture IL-2 identifies constituents of the expanded CD8 T cell effector pool that display stem-like features, preferentially survive, rapidly attain memory traits, resist exhaustion, and control chronic viral challenges. The cell-intrinsic synthesis of IL-2 by CD8 T cells attenuates the ability to receive IL-2-dependent STAT5 signals, thereby limiting terminal effector formation, endowing the IL-2-producing effector subset with superior protective powers. In contrast, the non-IL-2-producing effector cells respond to IL-2 signals and gain effector traits at the expense of memory formation. Despite having distinct properties during the effector phase, IL-2-producing and nonproducing CD8 T cells appear to converge transcriptionally as memory matures to form populations with equal recall abilities. Therefore, the potential to produce IL-2 during the effector, but not memory stage, is a consequential feature that dictates the protective capabilities of the response.